2009
DOI: 10.1016/s0030-6657(09)70135-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rhinitis in Polish population according to the ECAP (Epidemiology of Allergic Disorders in Poland) study

Abstract: Allergic rhinitis is common in Poland as it affects nearly 25% of the population and it is a major social problem. Standards of early detection and prevention of allergic rhinitis should be introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 11 publications
2
55
2
1
Order By: Relevance
“…The prevalence of allergy was 28.7% in this study compared to 42.3% self-reported by participants in another community based study done by Enroth S et al 13 Prevalence of rhinitis was reported to be ranging from 11.3% to 61.9% in previous Asian studies 12,15-17 and 22.5% in a European study 9 and 32% in a study done in Colombia 18 compared to 16.5% reported in this study. Allergic rhinitis has been found to adversely influence quality of patients by affecting mood, work, social functioning and sleep.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The prevalence of allergy was 28.7% in this study compared to 42.3% self-reported by participants in another community based study done by Enroth S et al 13 Prevalence of rhinitis was reported to be ranging from 11.3% to 61.9% in previous Asian studies 12,15-17 and 22.5% in a European study 9 and 32% in a study done in Colombia 18 compared to 16.5% reported in this study. Allergic rhinitis has been found to adversely influence quality of patients by affecting mood, work, social functioning and sleep.…”
Section: Discussioncontrasting
confidence: 42%
“…It thus has a huge socioeconomic impact and can adversely influence psychological wellbeing and quality of life. 4,9,10 Presence of one allergic disorder has been found to increase the risk of other allergic disorders affecting different organ systems. 11,12 These implications of allergic disorders can be minimized if strategies are planned for its early identification followed by appropriate interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This male predominance lasted up to age 15, then a reverse sex ratio was observed in post-pubescent girls and adult females [12]. Those data are slightly different from the findings of the Epidemiology of Allergic Disorders in Poland (ECAP) study performed in 2006-2008 [15,16]. Samolinski et al revealed that allergic rhinitis was more frequent (24.0%) in adult males aged 20-44 yrs than in females (21.2%).…”
Section: Discussionmentioning
confidence: 84%
“…To develop the algorithm, data from the Epidemiology of Allergy in Poland (ECAP) (www.ecap.pl) were used (110). Over 20 000 people responded to the study questionnaire, and almost 5000 were subjected to additional allergological tests.…”
Section: Electronic Monitoring Of Allergic Diseasesmentioning
confidence: 99%